The Relation Between von Willebrand Factor Plasma Concentration and Ultrasonograohic Doppler Findings in Pregnancies Complicated by Hypertensive Disorders (Texas Journal of Medical Science, 2022)
Hypertensive disorder of pregnancy is one of the most common complications in pregnancy forming a triad together with hemorrhage and infection. It affects about 10% of pregnancies and contributes for a significant maternal and perinatal mortality.